Total organic carbon and total nitrogen from DH-7B sediment core from the Dahu Lake, Ilan Plain - Abdur Rahman; Liang-Chi Wang; Kaoru Kashima; Hong-Chun Li; Huei-Fen Chen; Tien-Nan Yang (PANGAEA, 2025)
A 35-meter-long sediment core (DH-7B) was retrieved from Dahu Lake using a stainless-steel pipe mounted on a floating platform. The core was subsampled at 5-cm intervals with 1-cm thickness for diatom, stable isotope, and trace element analyses. For the analysis of carbon isotopic composition in organic carbon (δ^1^3C), powdered samples were decarbonated overnight with HCl. After complete removal of inorganic carbon, the residues were washed with ultrapure water (Milli-Q) by centrifugation three to four times, then dried at 60?°C overnight. The dried samples were encapsulated in tin and combusted at 1000?°C in a Flash 2000 Elemental Analyzer (Thermo Scientific). The resulting CO? was analyzed by isotope ratio mass spectrometry (IRMS; Delta V Advantage, Thermo Scientific) via a ConFlo interface using He as the carrier gas. The ^1^3C/^1^2C ratios were reported in δ notation relative to the Vienna Pee Dee Belemnite (VPDB) standard. The USGS 40 standard (L-glutamic acid, δ^1^3C = -26.39 ± 0.04 extperthousand; C content = 40.8%) was used to monitor instrument performance. Analytical precision was ±0.1 extperthousand for δ^1^3C and <10% for C content. Total nitrogen (N) content was measured simultaneously using the jump method in the same run.
In: Rahman, A et al. (2025): Typhoon and climate history of northeastern Taiwan during mid to late Holocene: inferred through the Dahu Lake sediment core, Ilan Plain [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982469